Wireless communication theory and applications - Biswas, Arumita; Chowdhury, Mainak (Cambridge University Press, 2017)
"Discusses design requirements, spectrum allocations and processes involved in popular wireless systems like cellular mobile system, wireless data service and satellite system"--